Strategies for preventing sexual harassment among adolescents: A literature review - Afaf Najibah; Endang Triyanto (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Sexual harassment refers to any unwelcome verbal, non-verbal, or physical conduct intended to, or resulting in, the violation of an individual's dignity, particularly through the creation of an intimidating, degrading, humiliating, or hostile environment. This form of harassment can lead to both immediate and long-term adverse effects on adolescent health. As previously noted, adolescents constitute a vulnerable group that must be safeguarded against such acts. One of the essential strategies for ensuring their protection involves the implementation of preventive measures. Purpose: To find out preventive measures that could be taken to prevent sexual harassment. Method: A systematic literature review guided by the PICO framework was employed. Literature searches were conducted using specific keywords combined with Boolean operators. The final selection of articles obtained through this process served as the basis for review in this study. Selected articles were subsequently extracted, evaluated for quality, and analyzed in a tabulated format. Results: The initial database search yielded a total of 1,447 articles. Following the screening and selection process based on the PRISMA flow diagram, 7 articles met the inclusion criteria and were included in the final analysis. The literature review identified several preventive programs targeting sexual harassment among adolescents, including Self-Defense Training, the RISE Program, policy development initiatives, as well as school-based interventions such as Benzies & Batchies and Boys, and the GlobalConsent program. Conclusion: Efforts to prevent sexual harassment in adolescents include self-defense training, awareness programs like RISE and Globalconsent, school policies, and resilience-building initiatives, all aimed at increasing knowledge and protection.